Comparison of Microbial Growth Between Commercial Formula and Blenderized Food for Tube Feeding. (3rd December 2018) - Johnson, Teresa W.; Milton, D. L.; Johnson, Kelly; Carter, Holly; Hurt, Ryan T.; Mundi, Manpreet S.; Epp, Lisa; Spurlock, Amy L.
Abstract: Background: Many healthcare facilities and providers prohibit blenderized tube feeding (BTF) for patients who request it due to concerns of high microbial load. The current project compared microbial loads of a standard ready‐to‐feed polymeric commercial formula (CF), a BTF made using baby food (BTF‐BF), and a BTF prepared from blending whole food (BTF‐WF), following food safety standards expected of U.S. hospitals. Methods: Three tube‐feeding formulas (CF, BTF‐BF, BTF‐WF) were prepared in a U.S. hospital and delivered in vitro to an unoccupied patient room. Samples were collected at zero hour, 2 hours, and 4 hours and compared for growth of aerobic microorganisms, Staphylococus aureus, coliforms, and Escherichia coli . The experiment was conducted in triplicate, 1 week apart. Results: No S. aureus or coliform/ E. coli were detected at any time point following preparation, and total bacterial count was well below acceptable limits. All 3 feeding formulas at zero hour, 2 hours, and 4 hours for each of the 3 sampling dates were acceptable for human consumption. Conclusion: Judicious BTF recipe selection and adherence to safe food handling provide a safe feeding substrate equivalent to CF in the hospital setting. Due to increased use and interest in BTF by patients and their caregivers, healthcare facilities may need to reexamine their policies prohibiting BTF use.